2010
DOI: 10.1186/1749-799x-5-56
|View full text |Cite
|
Sign up to set email alerts
|

Hemolymphangioma of the lower extremities in children: two case reports

Abstract: Background and purposeHemo-lymphangiomas are rare benign tumors that arise from congenital malformation of the vascular system. They are usually diagnosed at birth or early in childhood. The management of hemo-lymphangiomas in children remains challenging because complete resection is often difficult to be achieved and recurrences are common.MethodsWe present the case of two children with a mass on their left tibia. Imaging modalities, plain radiograph, Ultrasonography and Magnetic Resonance were used to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 10 publications
0
50
0
6
Order By: Relevance
“…Hemolymphangioma has been previously detected at the pancreas (5,7-12), spleen (13)(14)(15)(16), stomach (1,17), rectum (18), mediastinum (19)(20)(21), chest wall (22)(23)(24)(25), small intestine (26), extremities (3,27,28), cervix (29,30), pericardium (31), oral region (32), esophagus (33), axilla (34), retroperitoneal space (35,36), adrenal gland (37), abdomen (38), duodenum (4) and hepatica (39), as well as on the tongue (40,41) and orbit (42,43). However, to the best of our knowledge, no studies have reported this type of tumor in the waist region, as determined by a review of the medical literature until June 2014 using the PubMed database (http://www.ncbi.nlm.nih.gov/pubmed; accessed on 9th June 2014).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hemolymphangioma has been previously detected at the pancreas (5,7-12), spleen (13)(14)(15)(16), stomach (1,17), rectum (18), mediastinum (19)(20)(21), chest wall (22)(23)(24)(25), small intestine (26), extremities (3,27,28), cervix (29,30), pericardium (31), oral region (32), esophagus (33), axilla (34), retroperitoneal space (35,36), adrenal gland (37), abdomen (38), duodenum (4) and hepatica (39), as well as on the tongue (40,41) and orbit (42,43). However, to the best of our knowledge, no studies have reported this type of tumor in the waist region, as determined by a review of the medical literature until June 2014 using the PubMed database (http://www.ncbi.nlm.nih.gov/pubmed; accessed on 9th June 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hemolymphangioma is a congenital malformation that may be asymptomatic for a long period of time (3). This lesion is typically considered to be a benign and noninvasive disorder, characterized by the presence of dilated lymphatic spaces, extravasation of red blood cells, hemosiderin deposition and fibrosis (4).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations